Automatic capture management may cause unnecessary battery depletion in selective his‐bundle pacing. Issue 12 (23rd July 2020) - Wu, Hung‐Pin; Chen, Jan‐Yow; Lin, Kuo‐Hung; Chang, Kuan‐Cheng
Abstract: A routine change in the automatic capture management algorithm from "adaptive" to "off or monitor" is required to conserve device longevity in a permanent pacemaker with His‐bundle pacing. Abstract : A routine change in the automatic capture management algorithm from "adaptive" to "off or monitor" is required to conserve device longevity in a permanent pacemaker with His‐bundle pacing.